Effects of combined shear and thermal forces on destruction of microorganisms - Bulut, Sami (2001)
To investigate the effectiveness of physical forces in destroying microorganisms a heat resistant (D7Soc=20 min) Gram-positive vegetative bacterium, Microbacterium lacticum, a Gram-negative vegetative bacterium, Escherichia coli, and vegetative cells and spores of Gram-positive bacterium, Bacillus subtilis, were subjected to high mechanical energies using gelatin and maize grits as carriers. A twin screw extruder, a piston capillary rheometer and a rotational rheometer were used. When extruded with gelatin there was a strong correlation between the destruction of M. lacticum and the die wall shear stress and specific mechanical energy (SME). Within the limit of detection, no surviving M. lacticum could be detected in gelatin at the highest die wall shear stress of 409 kPa and a SME of 390 kJ -kg" , giving at least 5.3 decimal reductions. There was no surviving M. lacticum in maize grits at 289 kPa die wall shear stress and 294 kl-kg" SME, giving a 4.6 decimal reduction. The temperature at the extruder die remained below 61°C for all the extrusion experiments indicating that the bacterial destruction was due to combined shear and thermal forces rather than thermal forces alone. It was suggested that the thermal energy supplied during extrusion weakened the bacterial cell wall, making the cells susceptible to shear forces. A maximum 3.2 decimal reduction in the number of spores of B. subtilis in maize grits was obtained at 595 kPa die wall shear stress and 844 kJ.kg-1 SME, below 43°C extruder die temperature. There was no statistically significant difference in the survival of B. subtilis PS346 and B. subtilis PS361, which is a heat sensitive strain due to lack of (l- and P-SASP proteins, under the same extrusion conditions, suggesting that the main destruction mechanism was not heat. High reduction in the number of the viable spores suggested a possible "mechanical germination" inside the dynamic environment of the extruder. A 4.2 logarithmic reduction in the number of M lacticum in 30% (wwb) moisture content gelatin was observed in an unsheared sample in the piston capillary rheometer at 192 MPa and 60°C, showing that pressure could cause major destruction at high temperatures (60-75°C). No survival of M. lacticum was detected beyond 695 kPa shear stress and 64 MPa at 60°C, suggesting that an optimum combination of shear, thermal and pressure forces can cause an important reduction in the numbers of vegetative cells. Shearing of the microorganisms in the rotational rheometer in gelatin showed that the shear resistance of the microorganisms were different. Although only three species of bacteria were tested, it appeared that Gram-positive bacteria were more resistant to shear forces than Gram-negative bacteria. The results suggested that the destruction of the microorganisms at low shear forces (-3 kPa shear stress) was due to weakening of the bacterial cell wall at temperatures above 60°C. A maximum 1.4 logarithmic reduction in the number of M. lacticum was achieved after 4 min of shearing at 804 S-1 shear rate and 75°C. Based on the heat resistance data, thermal forces were not enough to cause significant destruction in the numbers of the microorganism, however, the temperature played a significant role by weakening the bacterial cell wall making it susceptible to shear forces. In this context, it is possible that there was a synergistic relationship between the shear and thermal forces. A shear D-value concept was introduced which was used to evaluate the shear resistance of microorganisms at different temperatures. Starch conversion (determined by differential scanning calorimeter) due to low temperature extrusion of maize grit inoculated with M. lacticum and spores of B.subtilis showed that there is a positive correlation between the bacterial destruction and the starch conversion. Up to 94% starch conversion was obtained during low temperature extrusion of maize grit where the estimated degree of starch conversion due to heat alone was 3.8%. The results suggested that if the shear forces can be optimally combined with thermal forces, an acceptable sterility can be achieved at significantly lower temperatures which would help to keep the quality of food products high.